Genetic diversity and population structure of some Nigerian accessions of Bambara groundnut (Vigna subterranea (L.) Verdc.,) using DArT SNP markers - Osundare, O.T.; Akinyele, B.O.; Odiyi, A.C.; Paliwal, R.; Oyatomi, Olaniyi; Abberton, Michael T. (Springer, 2023)
Bambara groundnut is one of the crops with inadequate molecular research to show its full potentials. Previous studies showed morphological diversity with inadequate information to confirm genetic variations. In the quest to reveal the genetic potentials, deoxyribonucleic acid (DNA) of the selected accessions was extracted through leaf samples at 3 weeks old, using Dellaporta Miniprep for Plant DNA Isolation procedure. The high quality DNA was sequenced using Diversity Arrays Technology (DArT) markers to unlock diversity among Bambara groundnut of Nigerian origin. Cluster analysis (neighbor-joining clustering) of the single nucleotide polymorphisms (SNP’s) were used to generate sub-population to show relatedness and differences. Seven sub-populations were generated with 5927 (50.13%) high quality DArT markers out of the 11,821 SNPs generated. This revealed high genetic diversity existed among the selected Bambara groundnut accessions in Nigeria. This also revealed that DArT markers were highly efficient in classifying the accessions based on molecular expressions. This study also identified markers responsible for genetic variation that could facilitate the characterization of larger collections for further utilization of genetic resources and most importantly Bambara groundnut for the purpose of crop improvement.